Homeless Youth and the Search for Stability - Karabanow, Jeff, 1969-; Hughes, Jean, 1949-; Frederick, Tyler, 1980-; Kidd, Sean, 1973- (Book collections on Project MUSE., 2018)
Youth are one of the fastest growing segments of the homeless population. Through qualitative and quantitative research and a comic book narrative, this book explores the often asked question: What happens when these young people leave the streets?